Microfluidic Blood Cell Preparation: Now and Beyond - Yu, Zeta Tak For (2014)
Blood plays an important role in homeostatic regulation with each of its cellular components having important therapeutic and diagnostic uses. Therefore, separation and sorting of blood cells has been of a great interest to clinicians and researchers. However, while conventional methods of processing blood have been successful in generating relatively pure fractions, they are time consuming, labor intensive, and are not optimal for processing small volume blood samples. In recent years, microfluidics has garnered great interest from clinicians and researchers as a powerful technology for separating blood into different cell fractions. As microfluidics involves fluid manipulation at the microscale level, it has the potential for achieving high-resolution separation and sorting of blood cells down to a single-cell level, with an added benefit of integrating physical and biological methods for blood cell separation and analysis on the same single chip platform. This paper will first review the conventional methods of processing and sorting blood cells, followed by a discussion on how microfluidics is emerging as an efficient tool to rapidly change the field of blood cell sorting for blood-based therapeutic and diagnostic applications.